Outlander : Season one, volume two - Brown, David; Roberts, Matthew B.; Heughan, Sam, 1980-; Balfe, Caitriona; McTavish, Graham; Menzies, Tobias, 1974-; Lewis, Gary; Verbeek, Lotte, 1982-; Gabaldon, Diana (Australia Universal Sony Picture Home Entertainment, 2015)
Claire Randall is a married combat nurse from 1945 who is mysteriously swept back in time to 1743. She is immediately thrown into an unknown world where her life is threatened. When she is forced to marry a chivalrous and romantic young Scottish warrior, a passionate affair is ignited that tears Claire's heart between two vastly different men in two irreconcilable lives.
Special features: An epic adaptation; The dresses & kilts of Outlander.
Producers, Matthew B. Roberts, David Brown.
Sam Heughan, Caitriona Balfe, Graham McTavish, Tobias Menzies, Gary Lewis, Lotte Verbeek.
Rated: MA15+
DVD; PAL ; Regions 2, 4, 5.
English dialogue; English subtitles for the deaf and hard of hearing.
Keywords: Nurses -- Great Britain -- Drama; Time travel -- Drama; Outlaws -- Scotland -- Drama; Man-woman relationships -- Drama; Scotland -- Drama; Great Britain; DVDs; DVD-Television.; Action and adventure television programs; Drama; Fantasy television programs; Fiction television programs; Television adaptations; Television series; Video recordings for the hearing impaired; Television adaptations; Television series